Badr War: The Effect of Victory on Arab Muslims - Rohman, Abd (Maliki Interdisciplinary Journal, 2024)
The Battle of Badr has played a central role in early Islamic history, having a significant impact on Arab Muslims. This article analyzes the influence of the Muslim victory in the Battle of Badr on the development and existence of the Islamic religion and the Arab Muslim community. By examining the events before, during, and after the battle, this article highlights how this victory strengthened Muslims’ faith and belief in Islamic teachings as well as their position in Arab society at that time. Factors such as military strategy, the courage of Muslim fighters, and help from Allah SWT are also analyzed in the context of their influence on the final outcome of the war and its implications for the Arab Muslim Ummah. Through this analysis, this article seeks to provide a better understanding of the role of victory in the formation of Islamic identity and religious development among Arab societies in the early Islamic period.